Exploring Development Challenges and Prospects: A Comprehensive Analysis of Development Studies in Venezuela - Yonathan Gerardo (GoAcademica Research & Publishing, 2023)
This journal article delves into the multifaceted landscape of development studies in Venezuela, shedding light on the country's ongoing socio-economic challenges, policy interventions, and potential pathways towards sustainable development. By examining the intricate interplay of political, economic, and social factors, this study seeks to provide a nuanced understanding of the complex dynamics that have shaped Venezuela's development trajectory. Through a comprehensive review of scholarly literature and empirical data, the article aims to contribute to a deeper comprehension of the obstacles and opportunities facing the nation, offering insights that can inform policy decisions and academic research in the field of development studies.